2018
DOI: 10.1002/adfm.201807535
|View full text |Cite
|
Sign up to set email alerts
|

Fine Control of Perovskite Crystallization and Reducing Luminescence Quenching Using Self‐Doped Polyaniline Hole Injection Layer for Efficient Perovskite Light‐Emitting Diodes

Abstract: Organic–inorganic hybrid perovskites (OHPs) are promising emitters for light‐emitting diodes (LEDs) due to the high color purity, low cost, and simple synthesis. However, the electroluminescent efficiency of polycrystalline OHP LEDs (PeLEDs) is often limited by poor surface morphology, small exciton binding energy, and long exciton diffusion length of large‐grain OHP films caused by uncontrolled crystallization. Here, crystallization of methylammonium lead bromide (MAPbBr3) is finely controlled by using a pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…According to previous study, when the solvent evaporates slowly, the crystal growth becomes slow and a larger grain size of perovskite can be formed. Here, both methods (adding MACl and DMSO) slow the crystal growth and gives rise to larger and more uniform perovskite crystals.…”
Section: Resultsmentioning
confidence: 82%
“…According to previous study, when the solvent evaporates slowly, the crystal growth becomes slow and a larger grain size of perovskite can be formed. Here, both methods (adding MACl and DMSO) slow the crystal growth and gives rise to larger and more uniform perovskite crystals.…”
Section: Resultsmentioning
confidence: 82%
“…The morphology and crystallinity of perovskite film, sensitive to the nucleation and growth of perovskite crystals, is one of the key components which affects the device performance of PSCs. The formation of perovskite crystals can be directly influenced by surface properties of the underlying HTL layer in p‐i‐n structured PSCs . Figure S4 shows the contact angle measurements of perovskite solutions formed on PEDOT : PSS (7.0°) and P2‐WSe 2 (3.6°) films, indicating better wettability of perovskite solution on P2‐WSe 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The formation of perovskite crystals can be directly influenced by surface properties of the underlying HTL layer in p-i-n structured PSCs. [35] Figure S4 shows the contact angle measurements of perovskite solutions formed on PEDOT : PSS (7.0°) and P2-WSe 2 (3.6°) films, indicating better wettability of perovskite solution on P2-WSe 2 . [36] When perovskite crystals are formed on foreign surface (PEDOT : PSS or P2-WSe 2 ), free energy required for the heterogeneous nucleation (DG heterogeneous ) becomes a dominant factor for the film formation, which depends on the contact angle (θ) as follow.…”
Section: Full Papermentioning
confidence: 99%
“…polarons), which serve as hole transport materials in electronic devices. 14,15 A number of research papers have demonstrated the fabrication and junction characteristics of indium tin oxide (ITO)/PANI/metal diode systems. [16][17][18][19] ITO coated glass is usually used as an electron injection contact, while PANI is a low work function polymer that enables hole injection to the electrode.…”
Section: Introductionmentioning
confidence: 99%